2016
DOI: 10.2131/jts.41.sp37
|View full text |Cite
|
Sign up to set email alerts
|

Chemical toxicology of reactive species in the atmosphere: two decades of progress in an electron acceptor and an electrophile

Abstract: Air pollutants such as diesel exhaust particles (DEP) are thought to cause pulmonary diseases such as asthma as a result of oxidative stress. While DEP contain a large number of polycyclic aromatic hydrocarbons, we have focused on 9,10-phenanthrenequinone (9,10-PQ) and 1,2-naphthoquinone (1,2-NQ) because of their chemical properties based on their oxidative and chemical modification capabilities. We have found that 9,10-PQ interacts with electron donors such as NADPH (in the presence of enzymes) and dithiols, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Quinone compounds are ubiquitously diffused in the environment as elements of the food chains or as air pollutants, for example in the diesel exhaust particles 53 . Quinones can also be generated in the body as a result of some xenobiotic metabolism through the cytochrome P450 system 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Quinone compounds are ubiquitously diffused in the environment as elements of the food chains or as air pollutants, for example in the diesel exhaust particles 53 . Quinones can also be generated in the body as a result of some xenobiotic metabolism through the cytochrome P450 system 36 .…”
Section: Discussionmentioning
confidence: 99%
“…9,10-PQ have been determined in various air samples ( e.g ., 130–730 pg/m 3 in samples from Riverside, LA; 6.1 ng/m 3 in sample from Birmingham, UK) and a metabolite of 9,10-PQ was detected in urine from a nonsmoker living in the suburban area of Kanazawa, Japan, indicating the necessity for basic studies of the effects of 9,10-PQ in vivo and in vitro . In our previous study, we showed that exposure of mice to 9,10-PQ caused an enhancement of allergic airway inflammation and recruitment of inflammatory cells. , Additionally, intraperitoneal administration of 9,10-PQ significantly suppressed endothelium-dependent vasorelaxation of rat aorta by acetylcholine and also increased the blood pressure, indicating that 9,10-PQ is a key molecular toxicant among atmospheric pollutants that increases health risks through an oxidative stress-dependent mechanism involving 9,10-PQ redox cycling.…”
Section: Discussionmentioning
confidence: 99%
“…ROS oxidize protein thiols to sulfenic acid (P-SOH) groups, which can undergo further oxidation to yield sulfinic acid (P-SO 2 H) and sulfonic acid (P-SO 3 H), leading to functional changes of the modified proteins. , Our in vivo and in vitro experiments indicated that Trx1 is a potential target for S -oxidation by 9,10-PQ, forming inactive forms Trx1-S 2 or Trx1-SO n H. Ichijo and co-workers demonstrated that Trx1-(SH) 2 is a physiological inhibitor of ASK1. Thus, oxidation of Trx1 by ROS activates ASK1 upon dissociation of oxidized Trx1 from the Trx1–ASK1 complex, inducing apoptosis via the activation of ASK1–p38 signaling .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycyclic aromatic hydrocarbons (PAHs) are both anthropogenic and naturally occurring ubiquitous environmental pollutants that are produced partly by combustion processes and are characterized by relatively high chemical stability. , Even so, they may be metabolically or abiotically converted to mutagenic quinone intermediates which are hazardous to human health. Human exposure to quinones occurs through direct contact with oxidized PAHs in the environment, through metabolic formation of PAH- ortho -quinones, through the aldo-keto reductase pathway, and through drugs that possess quinone moieties. , …”
Section: Introductionmentioning
confidence: 99%